2018
DOI: 10.1371/journal.pone.0193291
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and control training and capacity building during the Ebola epidemic in Guinea

Abstract: BackgroundDuring the 2014–2016 Ebola epidemic in West Africa, a key epidemiological feature was disease transmission within healthcare facilities, indicating a need for infection prevention and control (IPC) training and support.MethodsIPC training was provided to frontline healthcare workers (HCW) in healthcare facilities that were not Ebola treatment units, as well as to IPC trainers and IPC supervisors placed in healthcare facilities. Trainings included both didactic and hands-on components, and were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 2 publications
1
26
0
1
Order By: Relevance
“…As previous Ebola-related KAP surveys amongst HCW in Guinea during the EVD epidemic, we identified IPC training needs with regards to reported IPC training status and the described deficiencies in practices. The EVD epidemic has generated widespread awareness of the disease and left many HCW in the country with IPC training who had been without before [25][26][27]. Despite the increased post-Ebola efforts to improve IPC performance and VHF awareness in healthcare facilities, our study hints at a gap in IPC training in the N'zérékoré region, especially in rural areas.…”
Section: Discussionmentioning
confidence: 85%
“…As previous Ebola-related KAP surveys amongst HCW in Guinea during the EVD epidemic, we identified IPC training needs with regards to reported IPC training status and the described deficiencies in practices. The EVD epidemic has generated widespread awareness of the disease and left many HCW in the country with IPC training who had been without before [25][26][27]. Despite the increased post-Ebola efforts to improve IPC performance and VHF awareness in healthcare facilities, our study hints at a gap in IPC training in the N'zérékoré region, especially in rural areas.…”
Section: Discussionmentioning
confidence: 85%
“…24 As indicated by previous surveys of infectious diseases during epidemics, infection control training is important to increase awareness and improve the personal hygiene performance. 22,[25][26][27][28] Our study has 2 main limitations. First, our results are based on a non-probabilistic sampling strategy.…”
Section: Discussionmentioning
confidence: 96%
“…During the 2014 EVD outbreak in Guinea, researchers demonstrated that IPC training was feasible in emergency settings and that it resulted in knowledge improvement 10. In Guinea, the knowledge of Ebola among HCW was relatively high.…”
Section: Discussionmentioning
confidence: 99%